Svetáci - Podskalsky, Zdenek; Valert, Frantisek; Sovak, Jiri; Brodsky, Vlastimil; Libícek, Jan (Bontonfilm, 2004)
An evergreen of Czechoslovak cinema and one of the most popular comedies ... This film owes its undying popularity to a brilliant screenplay and stellar casting that brought together the biggest talents of Czech comedy such as Jiri Sovak, Vlastimil Brodsky, Jan Libicek, Jirina Bohdalova, Jirina Jiraskova and Iva Janzurova. In the film three village bricklayers decide to have a taste of the big world and meet true ladies of society while working in Prague. And to do so in style, the uneducated simpletons hire an old First Republic gentleman, played by Oldrich Novy, to polish their social skills. [freshfilmfest.net]